Design of a Novel Online, Modular, Flipped-classroom Surgical Curriculum for East, Central, and Southern Africa. Issue 1 (2nd March 2022) - Parker, Andrea S.; Hill, Katherine A.; Steffes, Bruce C.; Mangaoang, Deirdre; O'Flynn, Eric; Bachheta, Niraj; Bates, Maria F.; Bitta, Caesar; Carter, Nicholas H.; Davis, Richard E.; Dressler, Jeremy A.; Eisenhut, Deborah A.; et al.
Abstract : Objective: We describe a structured approach to developing a standardized curriculum for surgical trainees in East, Central, and Southern Africa (ECSA). Summary Background Data: Surgical education is essential to closing the surgical access gap in ECSA. Given its importance for surgical education, the development of a standardized curriculum was deemed necessary. Methods: We utilized Kern's 6-step approach to curriculum development to design an online, modular, flipped-classroom surgical curriculum. Steps included global and targeted needs assessments, determination of goals and objectives, the establishment of educational strategies, implementation, and evaluation. Results: Global needs assessment identified the development of a standardized curriculum as an essential next step in the growth of surgical education programs in ECSA. Targeted needs assessment of stakeholders found medical knowledge challenges, regulatory requirements, language variance, content gaps, expense and availability of resources, faculty numbers, and content delivery method to be factors to inform curriculum design. Goals emerged to increase uniformity and consistency in training, create contextually relevant material, incorporate best educational practices, reduce faculty burden, and ease content delivery and updates. Educational strategies centered on developing an online, flipped-classroom, modular curriculum emphasizing textual simplicity, multimedia components, and incorporation of active learning strategies. The implementation process involved establishing thematic topics and subtopics, the content of which was authored by regional surgeon educators and edited by content experts. Evaluation was performed by recording participation, soliciting user feedback, and evaluating scores on a certification examination. Conclusions: We present the systematic design of a large-scale, context-relevant, data-driven surgical curriculum for the ECSA region. Abstract : Mini-abstract: We describe the design of a large-scale, standardized, surgical curriculum for trainees in East, Central, and Southern Africa using Kern's 6-step approach. This systematic process resulted in the development of an online, modular, flipped-classroom surgical curriculum, written by regional surgical educators and with relevance to the sub-Saharan African context.